2010
DOI: 10.1063/1.3388385
|View full text |Cite
|
Sign up to set email alerts
|

Optical frequency shot-noise suppression in electron beams: Three-dimensional analysis

Abstract: A predicted effect of current shot-noise suppression at optical-frequencies in a drifting charged-particle-beam and the corresponding process of particles self-ordering are analyzed in a one-dimensional ͑1D͒ model and verified by three-dimensional numerical simulations. The analysis confirms the prediction of a 1D single mode Langmuir plasma wave model of longitudinal plasma oscillation in the beam, and it defines the regime of beam parameters in which this effect takes place. The suppression of relativistic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Past work on noise suppression resulting from plasma oscillations has found that 3D models lead to weaker noise suppression [14,15]. In our 1D model we assume a rigid sheet of charge that moves uniformly due to the average longitudinal field, whereas in reality each particle moves independently.…”
Section: Validity Of 1d Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Past work on noise suppression resulting from plasma oscillations has found that 3D models lead to weaker noise suppression [14,15]. In our 1D model we assume a rigid sheet of charge that moves uniformly due to the average longitudinal field, whereas in reality each particle moves independently.…”
Section: Validity Of 1d Modelmentioning
confidence: 99%
“…2.6). This may correspond to analogous differences between 3D and 1D models in suppression through plasma oscillations [14,15].…”
Section: Extension To 3d Modelmentioning
confidence: 99%
See 3 more Smart Citations